Analysis of the correlation between the degree of liver fibrosis and the severity of depressive symptoms in patients with NAFLD - Skurat, Катерина; Koval, Ірина (Psychosomatic Medicine and General Practice, 2021)
This is a conference abstract from the III Scientific and Practical Conference "Psychosomatic medicine: science and practice". It is dedicated to the analysis of the correlation between the degree of liver tissue damage and the severity of depressive symptoms in patients with nonalcoholic fatty liver disease.